ANALISIS PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN HOTEL BINTANG LIMA PEKANBARU - Nico Pratama Onasie; Jushermi '; Henny Noviasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to analyze the effect of partial and simultaneous variable service quality and price on customer satisfaction levels Five Star Hotels in Pekanbaru. The study was conducted on December 1, 2013 until May 10, 2014 in the city of Pekanbaru Riau.Di province in this study consisted of five variables: the dependent variable and four independent variables. These variables are the Customer Satisfaction (Y), Interaction Quality (X1) Physical Environment Quality (X2) Outcomes Quality (X3) Price (X4). The study was conducted using a sample of 100 people. studies using random sampling techniques. In terms of data analysis, research using multiple linear regression analysis with SPSS (Statistical Package for Social Science) version 20.0. Known quality of service and price positive and significant impact on consumer satisfaction Five Star Hotels Pekanbaru either simultaneously or partially. The variables are the dominant influence on the Five Star Customer Satisfaction Pekanbaru is the variable quality of the Physical Environment. So the consumer needs for quality interaction, physical environment quality, quality and quality results at an affordable price can increase customer satisfaction Pekanbaru. For Five Star Hotels, the management of the hotel should continue to improve the quality of interaction and quality of service associated with the corresponding consumer expectations, as well adjust the price in accordance with customer expectations.Keywords: Service Quality, Interaction Quality, Physical Environment Quality, Outcomes Quality, Price, Customer Satisfaction